Pangea rifting and onward pre-Central Atlantic opening as the main ore-forming processes for the genesis of the Aouli REE-rich fluorite–barite vein system, Upper Moulouya District, Morocco. (August 2015) - Margoum, Daoud; Bouabdellah, Mohammed; Klügel, Andreas; Banks, David A.; Castorina, Francesca; Cuney, Michel; Jébrak, Michel; Bozkaya, Gulcan
Highlights: We performed REE, fluid inclusions and Sr and S isotope analysis. Fluorite mineralization is related to Pangea rifting and pre-Atlantic opening. Ore-fluids were hot saline sedimentary brines from 2 distinct sources. Water–rock interactions released REE and metals to the ore fluids largely from the granites. Mixing and cooling were the main causes of ore deposition. Abstract: The Aouli fluorite–barite ± sulphides vein system in the Upper Moulouya District of Central Morocco is hosted in a folded and low to medium grade sedimentary and volcanic rocks, unconformably overlaid by Permo-Triassic to Cretaceous red beds and limestones. Intrusion of the hydrothermally altered multiphase ca. ∼330–319 Ma Aouli granite batholith has contact metamorphosed the host rocks to a metamorphic assemblage of cordierite, andalusite, chlorite, muscovite, and biotite ± sillimanite ± garnet. The mineralized structures that consist mostly of quartz, fluorite, and barite occur principally as ENE–WSW, WNW–ESE, and E–W-trending trans-tensional steeply dipping veins, veinlets and en echelon tension gash fillings. Irrespective of colour, location, paragenesis and textural position within the mineralized vein structure, the fluorite is characterized by high total REY contents ranging from 250 to 662 ppm, distinctive positive Eu and Y anomalies, and middle rare-earth element enrichment. Fluid inclusion data indicate that the ore-forming fluids correspond to evolved NaCl–CaCl2 + other cations sedimentary (94–174 °C), saline (14–24 wt% NaCl equiv.) brines. The strontium isotopic compositions of fluorite ( 87 Sr/ 86 Sr = 0.710155–0.712293) and barite (0.710215–0.701401), along with the Liassic dolomitized limestones (0.707867–0.708140) are more radiogenic than the Cambro-Ordovician and Triassic–Early Jurassic seawater values, with the Aouli Late Variscan granite (0.70814 ± 12) and the Triassic arkoses (0.709839–0.712313) displaying the highest 87 Sr/ 86 Sr ratios. Barite separates show uniform δ 34 S ratios of +11‰ to +13.4‰ consistent with Permian–Triassic seawater sulphate. The calculated REY fluid compositions along with fluid inclusion, strontium and sulphur isotope data point to the role of hot sedimentary brines with fluid–rock interaction at high fluid/rock ratios. The fluid system is likely related to the Pangea rifting and subsequent Central Atlantic opening during Permian–Triassic time. The fluorite–barite mineralization is likely due to mixing at the basement–cover interface of an ascending deep-seated fluid that equilibrated with Variscan crystalline basement rocks and cooler more dilute formation water.